Politična kultura med diktaturo in demokracijo - Kolenc, Janez (Teorija in praksa, 2006)
The article is dealing with the critics of the framework of the programme of social and economics reforms which has proposed by Slovene government in the year 2005. Critical analysis revealed a series of inconsistencies, contradictories and disagreements in the text of the proposal of reforms. The article is especially referred to the question of the quality of the reform proposal and the question of political democracy and political culture in Slovenia. Author reveal a lot of correlations between reform proposal and the condition of political culture in Slovenia claiming, that political culture in Slovenia is fragmentary and so is divided on several subcultures. Author finds important correlation between reform proposal and division of political culture on mass and elite one, from where proceeds the conclusion that Slovenian electoral body in specific social and historical circumstances could decided for dictatorship or democracy. Reforms of economic and political system in Slovenia are urgent, however not that kind as presented by Slovenian government.
Keywords: Družbene reforme; Social reform; Political culture; Politična kultura; Economics; Ekonomija; Politics; Politika; Slovenia; Slovenija